(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Surgical assistance in thyroid surgeries is a must needed thing for smooth outcome of various types of surgery subplatysmal flap retraction is always a key step for that, conventional use of ligating it with drape seats or pulling it away with thyroid retractors always require a decent cost instruementation or engaged manpower this can often lead to prolonged time and its related fatigue among the assistant surgeons To overcome this problem different sets of ideas can be implemented and had been developed for continuous exposure during surgery.1-3 Thyroidectomy is an established procedure where different types of Thyroidectomy deals with the pathological variation of thyroid diseases, Thyroidectomy is a very intricate surgical procedure and having many surgical steps which are supposed to be performed very very meticulously , securing the subplatysmal flap raises up and down by proper retraction is the key step for thyroid gland to be rejected exposure , a simple rubber band technique is a very effective , safe , cheap and home made tool which we use in our thyroid surgery and can be reliable upon , it’s a simple , safe and cost effective idea and improvisation we discuss in our study here.